A educação ambiental por meio da ludicidade: uma experiência em escolas do entorno do Parque Estadual do Utinga - BAÍA, Maria da Conceição Ferreira (Universidade Federal do Pará, 2020)
One of the main problems of contemporary society is the degradation of the environment. Humanity is facing a big challenge - the preservation of natural resources and consequently the preservation of his own existence. Given this situation, the Environmental Education (EE) is presented as a way to educate more in a comprehensive and complete way. In this context, the “Novo Encanto” Association in partnership with the State Secretary of Environment (SEMA) perform planned actions for elementary school students from public schools in Ananindeua - PA, located around the PAB, with the aim to study the use of the playful as a strategy to sensitize the children of the importance of the place as a space for recreation, environmental reserve, biodiversity and water resources.